External rewards and positive stimuli promote different cognitive control engagement strategies in children. (August 2020) - Jin, Xiaoyu; Auyeung, Bonnie; Chevalier, Nicolas
Abstract: In everyday life, children often need to engage control in emotionally or motivationally relevant contexts. This study disentangled and directly compared the respective influences of external rewards and positive stimuli on childhood cognitive control. We expected external rewards to promote proactive cognitive control and positive stimuli to impair proactive control, especially in younger age. EEG data were recorded while children (5–6 years old and 9–10 years old) and adults completed a cued task-switching paradigm in three conditions: positive-stimulus, external-reward and control conditions. Provision of reward resulted in more accurate but slower responses, and more pronounced cue-locked posterior positivity, potentially suggesting general proactive mobilisation of attention (i.e., readiness). Despite no effects on behaviour, the presentation of positive stimuli was unexpectedly associated with a greater cue-locked extended slow-wave when task cues were presented ahead of targets (i.e. proactive-control possible) in younger children, suggesting greater proactive cue preparation. In contrast to our hypothesis, both external rewards and positive stimuli seem to promote different types of proactive approaches in children.